Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Kinerja Karyawan Produksi Pada PT Sumber Makmur Jambe Kabupaten Tangerang - Hardy Fajar Muarif; Ibrahim Bali Pamungkas (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract The purpose of this study was to determine the effect of leadership style and compensation on the performance of production employees at PT Sumber Makmur Jambe, Tangerang Regency. The method used was quantitative with an associative approach. The sampling technique used saturated samples, namely 60 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results showed that leadership style had an effect on employee performance with a t-value of 2.005> t-table 2.001, simple linear regression Y = 26.831 + 0.198X1 and a determination coefficient of 6.5%. Compensation also affects employee performance with a calculated t value of 2.039 > Ttable 2.001, simple linear regression Y = 26.054 + 0.274X2 and a coefficient of determination of 6.7%. Simultaneously, leadership style and compensation affect employee performance with a regression equation of Y = 19.494 + 0.173X1 + 0.243X2. The correlation coefficient is 0.341 with a low relationship. The coefficient of determination is 11.6%. The hypothesis test obtained a calculated F value > F table or (3.749 > 3.160).